Assessment of out-of-plane behavior of rammed earth walls by pull-down tests. Issue 2 (17th February 2019) - Wangmo, Phuntsho; Shrestha, Kshitij C.; Miyamoto, Mitsuhiro; Aoki, Takayoshi
ABSTRACT: This article reports pull-down tests performed on rammed earth construction in Bhutan. The pull–down specimens involved an old rammed earth building component as well as a newly prepared rammed earth wall. Both the wall specimens were tested in out-of-plane direction. Theoretical rigid body formulation and finite element (FE) models were developed to predict the response of the rammed earth structures under out-of-plane loading. The validated FE model was further extended to parametric study of material and physical characteristics of rammed earth construction and their effect on critical response quantities. The change in elastic modulus showed effect in the pre-cracking phase of the wall. Density of rammed earth on the other hand affected the post-peak response of the rammed earth wall. Furthermore, an increase in the physical characteristics, namely, the thickness of wall and the vertical superimposed load on top of the wall, enhanced the rocking resistance capacity of the out-of-plane loaded rammed earth walls.